Link Between Aeration in the Rhizosphere and P-Acquisition Strategies: Constructing Efficient Vegetable Root Morphology - Wang, Rui; Shi, Weiming; Li, Yilin (Frontiers in Environmental Science, 2022)
Excessive application of phosphate fertilizer is common in vegetable fields and causes, deterioration of the rhizosphere environment, i.e., the soil oxygen (O2) environment, which further constrains root morphology construction and limits vegetable yield. Nevertheless, the interaction between root morphology and the response of the rhizosphere O2 environment to vegetable P utilization has rarely been reported. Therefore, we carried out an experiment applying different concentrations of O2 generator, 10%, 30%, 50%, and 80% urea hydrogen peroxide (as pure nitrogen) instead of urea as a top dressing in the rhizosphere to study the effect on root morphology and P adsorption and its mechanism. We found that there were O2-deficient and P-deficient zones in the rhizosphere, and oxygenation could alleviate the rhizosphere O2 and P consumption in roots. The rhizosphere O2 concentration was maintained at approximately 250.6 µmol L-1, which significantly promoted total root length, root volume, average diameter, and root activity by 29.0%, 30.9%, 3.9%, and 111.2%, respectively. Oxygenation promoted organic P mineralization and increased the Olsen-P content in the rhizosphere. The characteristics of root morphology and increased available P in the rhizosphere jointly contributed to high P absorption and utilization, and the P use efficiency was improved by 9.3% and the shoot P accumulation by 10.9% in the 30% urea hydrogen peroxide treatment compared with CK. Moreover, this treatment also improved yield and quality, including vitamin C and soluble sugar content. However, at a still higher O2 concentration (260.8 µmol L-1), vegetable growth exhibited O2 damage, resulting in reduced yield and quality. Our study provided new insight into constructing efficient root morphology by regulating the rhizosphere O2 environment to improve vegetable yield and quality, as well as to increase P use efficiency in vegetable fields.